2021
DOI: 10.1210/clinem/dgab859
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork, Targets, Technology, and Tight Control in Newly Diagnosed Type 1 Diabetes: the Pilot 4T Study

Abstract: Context Youth with type 1 diabetes (T1D) do not meet hemoglobin A1c (HbA1c) targets. Objective To assess HbA1c outcomes in children with new onset T1D enrolled in the Teamwork, Targets, Technology and Tight Control (4T) Study. Method HbA1c levels were compared between the 4T and Historical cohorts. HbA1c differences between cohorts were estimated using locall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…This qualitative study is part of a previously reported pragmatic research study 5,14 and is a follow‐up to previously reported qualitative results from in‐person delivery of CGM initiation during the Type 1 diabetes new‐onset period for families of youth with Type 1 diabetes 8 . In brief, the main study delivers a clinical protocol to initiate CGM within 30 days of Type 1 diabetes diagnosis (mean time to CGM initiation = 7 days 14 ) and provides 30 days of CGM supplies while insurance approval is sought. Families receive Dexcom G6 CGM (Dexcom Inc.); the rationale for which has been previously described 8 .…”
Section: Methodsmentioning
confidence: 99%
“…This qualitative study is part of a previously reported pragmatic research study 5,14 and is a follow‐up to previously reported qualitative results from in‐person delivery of CGM initiation during the Type 1 diabetes new‐onset period for families of youth with Type 1 diabetes 8 . In brief, the main study delivers a clinical protocol to initiate CGM within 30 days of Type 1 diabetes diagnosis (mean time to CGM initiation = 7 days 14 ) and provides 30 days of CGM supplies while insurance approval is sought. Families receive Dexcom G6 CGM (Dexcom Inc.); the rationale for which has been previously described 8 .…”
Section: Methodsmentioning
confidence: 99%
“…We have previously developed a system for transmitting data from an individual's CGM into our electronic medical records using Apple Health-Kit on iOS devices [ During the Pilot 4T study, remote glucose monitoring was developed and then initiated for the next 89 (out of the 135) children and families who consented to participate in remote data review (i.e., remote monitoring). HbA1c at 12 months postdiagnosis in the Pilot 4T cohort was 0.58% lower than the historic cohort and those Pilot 4T patients receiving remote monitoring had a HbA1c 0.14% lower than patients in the Pilot 4T cohort not receiving remote monitoring at 12 months post-diagnosis [21]. In addition, our 4T program demonstrates that CGM initiation during the new-onset period is feasible and well accepted by youth and their families [31].…”
Section: Teamwork Targets Technology and Tight Control Study Overviewmentioning
confidence: 69%
“…By focusing on the cadence of reviews, study 2 will help to determine whether a more pragmatic and generalizable cadence of reviews yields comparable outcomes while increasing remote data review capacity by clinical team members and testing for non-inferiority. Assessing a more pragmatic cadence of review will define how TIDE can be translated to other clinical settings in a time and cost-efficient manner [21,22]. We will also compare outcomes to historical controls in our program and contemporaneous outcomes in other T1D populations.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the prospective single-centre 4T (Teamwork, Targets, Technology and Tight Control) Study conducted at a diabetes centre in the USA compared glucose metrics in the first year after diagnosis with historical controls. When CGM was started within the first month of diagnosis together with defined glucose goals, after the nadir at 4 months, HbA1c was lower and there was a low incidence of hypoglycaemia and no episodes of severe hypoglycaemia [33 ▪▪ ].…”
Section: Continuous Glucose Monitoringmentioning
confidence: 99%